Впровадження геліосушарок для виробництва висушених сільськогосподарських продуктів - Коробка, С. В.; Стукалець, І. Г.; Бабич, М. І.; Баранович, С. М.; Скляр, Олександр Григорович; Болтянський, Борис Володимирович; Скляр, Радміла Вікторівна; Korobka, S.; Stukalets, I.; Babych, M.; Baranovych, S.; Sklіar, Oleksandr; et al. (Запоріжжя : 2024, 2024)
UA: У роботі детально представлено процес сушіння яблук у геліосушарці. Описано розробку нової конструкції сонячної сушильної установки, виготовленої з доступних матеріалів для сушіння сільськогосподарської продукції з ефективним використанням відновлюваних джерел енергії, зокрема сонячної, з урахуванням екологічних та економічних умов України. Розроблено нову конструкцію геліосушарки для сушіння сільськогосподарської сировини. У цій установці можна висушувати різні види сільськогосподарської продукції, використовуючи різні матеріали для покриття сушильної камери, такі як полікарбонат, скло, поліетилен, гофрований метал (для сушіння трав) тощо. Розроблено режими роботи геліосушарки з дзеркальним концентратором, тепловим акумулятором і додатковим осушувачем теплоносія, а також враховано циклічність процесу сушіння. Визначено кінетичні параметри вологовіддачі яблук, які відображають часові зміни кінетики їх сушіння. EN: The paper presents in detail the process of drying apples in a solar dryer. The development of a new design of a solar drying plant made of available materials for drying agricultural products with efficient use of renewable energy sources, in particular solar energy, taking into account the ecological and economic conditions of Ukraine, is described. A new solar dryer design for drying agricultural raw materials has been developed. In this plant, different types of agricultural products can be dried using different materials to cover the drying chamber, such as polycarbonate, glass, polyethylene, corrugated metal (for drying herbs), etc. The modes of operation of the solar dryer with a mirror concentrator, a heat accumulator and an additional coolant dryer have been developed, and the cyclic nature of the drying process has also been taken into account. The kinetic parameters of the moisture release of apples were determined, which reflect the temporal changes in the kinetics of their drying. As a result of conducting experiments during which more than 20 types of agricultural products were dried, it was established that the increased air temperature in the solar dryer significantly reduces the drying time, speeding up the process by 2.5-4.5 times compared to traditional drying in the sun. It is known that the loss of vitamins is inversely proportional to the duration of drying. This article presents the results of drying apples, which demonstrate that the duration of drying apples in a solar dryer is 3.4 times less than when drying in the fresh air. The solar dryer can be placed on any south-facing site to make the most of solar energy. The higher the air temperature, the greater the temperature difference between the air in the solar dryer and the surrounding environment. The convective solar dryer is light and easy to transport and can be moved or rotated in the direction of the sun during the day. The large-sized version of the solar dryer is mainly intended for peasant farms. Easy to manufacture, this dryer can be used both in farms and in private households.
Implementation of solar dryers for the production of dried agricultural products
Keywords: сонячна енергія; геліосушарка; температурно-вологісні поля; тепломасоперенесення; інтенсифікація; конвективне сушіння; solar energy; solar dryer; temperature and humidity fields; heat and mass transfer; intensification; convective drying